Análise de atuação indevida do ERAC em desenergização de subestação, influenciada pela desaceleração de motores e proposta de lógica utilizando a função ANSI 81U com dois estágios de tensão de bloqueio e temporização - Borges, Adriano (2020)
The stability of the SEP is a major concern for System Operators worldwide. Several actions and controls are taken when a major disturbance occurs, with the aim of finding a new balance point, minimizing the disconnection of loads and avoiding generalized blackouts. One of the most important controls is the Under Frequency Load Shedding (UFLS), in Brazil called the Regional Load Relief Scheme (ERAC). This function has already avoided several blackouts with selective load cuts by underfrequency, bringing the system to the load-generation balance. ERAC’s performance is important for the stability of the National Interconnected System (SIN), however, the improper performance of this function generates problems for concessionaires, such as customer dissatisfaction and fines imposed by the National Electric Energy Agency - ANEEL. Following this reasoning, this paper analyzes the reliability of the ERAC system in SIN disturbances and some undue actions, influenced by the deceleration of induction motors. Then, the characteristic of the voltage wave that arises due to the influence of the motors is analyzed, with the aid of the DIgSILENT software, as well as which are the ideal settings for commercial underfrequency relays in the South region. This analysis was aided by the ANATEM software, by oscillographic records of actual actions by the SIN and undue actions by the RGE concessionaire underfrequency relays. Finally, a new ERAC schemes is proposed, obtained from two settings for the blocking voltage. As result, there is the blocking of the ANSI 81U function during engine the deceleration and the guarantee of the correct performance of the ERAC when it is requested.